A multiphase mixture model for substrate concentration distribution characteristics and photo-hydrogen production performance of the entrapped-cell photobioreactor. (April 2015) - Guo, Cheng-Long; Cao, Hong-Xia; Pei, Hong-Shan; Guo, Fei-Qiang; Liu, Da-Meng
Highlights: A multiphase mixture model is developed for the entrapped-cell photobioreactor. Substrate concentration distribution and photo-hydrogen production are predicted. Interaction mechanism between biochemical reaction and transfer process is revealed. The effects of difference operation parameters are investigated. Abstract: A multiphase mixture model was developed for revealing the interaction mechanism between biochemical reactions and transfer processes in the entrapped-cell photobioreactor packed with gel granules containing Rhodopseudomonas palustris CQK 01. The effects of difference operation parameters, including operation temperature, influent medium pH value and porosity of packed bed, on substrate concentration distribution characteristics and photo-hydrogen production performance were investigated. The results showed that the model predictions were in good agreement with the experimental data reported. Moreover, the operation temperature of 30 °C and the influent medium pH value of 7 were the most suitable conditions for photo-hydrogen production by biodegrading substrate. In addition, the lower porosity of packed bed was beneficial to enhance photo-hydrogen production performance owing to the improvement on the amount of substrate transferred into gel granules caused by the increased specific area for substrate transfer in the elemental volume.